Pembentukan Karakter Peduli Lingkungan Melalui Pembiasaan Kebersihan oleh Guru Pendidikan Agama Islam di SMP Negeri 1 Selong - Nurul Jum’ah Fathi Huballoh (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study examines how an Islamic Religious Education (PAI) teacher fosters students’ environmental care character through school hygiene habituation at SMP Negeri 1 Selong.Methods – This study employed a descriptive qualitative case-study design. Data were collected through non-participant observations of school hygiene routines, semi-structured interviews with key informants (the PAI teacher and the principal), and document review (e.g., class duty rosters and school hygiene rules). The analysis followed an iterative process of coding, categorizing, and theme development, with cross-checking of evidence across sources to enhance credibility.Findings – Hygiene was institutionalized as a shared school norm through class duty rosters, periodic communal clean-ups, and strategically placed waste facilities. The PAI teacher framed hygiene not only as ritual purity but also as responsibility for reducing plastic waste and pollution and linked this value to lesson content. Habituation was reinforced through teacher modeling, plastic reduction practices (tumbler use and bottle collection), and behavioral reinforcement via rewards and educational consequences. Key constraints included less supportive home habits and inconsistent compliance among a minority of students. Research Implications – Sustaining a clean-school culture requires consistent teacher exemplars, principal support, adequate facilities, and collaborative routines. The findings are context-bound to a single school with a limited set of informants.